2005
DOI: 10.1590/s1516-35982005000200029
|View full text |Cite
|
Sign up to set email alerts
|

Análise multivariada das medidas morfométricas de potros da raça Mangalarga Marchador: análise de componentes principais

Abstract: RESUMO -Objetivou-se, com este trabalho, a avaliação morfométrica de potros da raça Mangalarga Marchador, a partir da análise de componentes principais. As medidas corporais foram efetuadas na semana do nascimento dos potros, em 55 potros e 41 potras; aos seis meses de idade, em 35 potros e 37 potras; e aos 12 meses de idade, em 19 potros e 31 potras. Foram efetuadas 25 mensurações lineares, envolvendo altura, comprimento, largura e perímetros, e 11 mensurações angulares. Na avaliação dos animais com 12 meses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The F-MB group showed the greatest variation with up to five PC. PINTO et al (2005) observed an even greater number of PC finding seven components to explain a minimum percentage of 80% of the total variation of horses less than 12 months old. Therefore, it is suggested that the younger the animal, the greater the variance of the body parts.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The F-MB group showed the greatest variation with up to five PC. PINTO et al (2005) observed an even greater number of PC finding seven components to explain a minimum percentage of 80% of the total variation of horses less than 12 months old. Therefore, it is suggested that the younger the animal, the greater the variance of the body parts.…”
Section: Resultsmentioning
confidence: 94%
“…Comparisons of individual measurements demonstrate that trot horses have smaller widths between the eyes and jaw, as well as proportionally longer segments in the forelimbs, and thinner circumferences in the lower parts of these limbs (STAIGER et al, 2016). The selection of the MM breed gave the animals a smaller head, shorter body length, a larger diameter of the bone rays and an increase in the size of these animals within the standard values of the breed (PINTO et al, 2005). However, similarities and differences in conformation within the race can be noticed in relation to gender and type of marcha, especially regarding measurements related to limb flexion, frequency, and stride length (SANTIAGO et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This strong dimensional reduction had already been reported in other species, but the present study is the first to indicate this possibility also in goats. In newly born Mangalarga Marchador horses, PINTO et al (2005) applied PCA for morphometric measurements and observed a reduction from 25 to seven and nine in females and males, respectively, while for angular measurements the reduction was from 11 to six and seven traits in females and males, respectively. BARBOSA et al (2005) whole leg weight; breast weight; abdominal fat pad weight; weights of liver, gizzard, and heart; and carcass dry matter, fat, and crude protein contents, and of the11 quail carcass traits assessed, only four were sufficient for explaining a large variance percentage.…”
Section: Principal Components Analysismentioning
confidence: 99%
“…PINTO et al (2005), used PCA to identify redundant morphometric traits in Mangalarga Marchador horses. Similarly, BARBOSA et al (2005), applied PCA to 33 carcass traits in a swine population and identified 17 redundant traits.…”
Section: Introductionmentioning
confidence: 99%